PUBLIC SERVICE DELIVERY IN THE AGE OF DIGITALIZATION: CHALLENGES, ADAPTATION, AND INSTITUTIONAL RESPONSES - Rachel Vivian Sitorus; Dara Aisyah; Muhammad Imanuddin Kandias Saraan (Academic Solution Publisher, 2025)
Digitalization has significantly reshaped the design and delivery of public services, offering potential gains in efficiency, transparency, and citizen engagement, yet producing uneven outcomes across public institutions. This article analyzes the transformation of public service delivery in the digital era by emphasizing institutional capacity, adaptive governance, and citizen-centered approaches. Using a qualitative literature review, the study synthesizes theoretical, empirical, and policy-oriented research from major international databases through thematic analysis informed by digital-era governance perspectives. The findings demonstrate that digitalization constitutes a socio-institutional transformation rather than a purely technological process. Institutional capacity reflected in leadership commitment, regulatory adaptability, inter-organizational coordination, and organizational learning emerges as a critical determinant of successful digital public services. Additionally, citizen-centered and inclusive governance is essential to mitigate risks of digital exclusion and inequality. Integrating institutional capacity with responsive, citizen-oriented governance frameworks is therefore crucial for creating sustainable public value and effective digital service ecosystems in the public sector.